American horror story. Apocalypse. The complete 8th season [videorecording (DVD)]. - Paulson, Sarah, 1974-; Bates, Kathy, 1948-; Fern, Cody; Peters, Evan, 1987- (20th Century Fox Home Entertainment, 2019)
After a nuclear apocalypse, the world's chosen elite survive in secure Outposts created by the mysterious Cooperative. On the American West Coast, Ms. Wilhemina Venable and Ms. Miriam Mead run Outpost Three with an iron fist. The unexpected arrival of Michael Langdon, a Cooperative representative determined to save society with a secret paradise, throws their order into chaos. However, underneath the surface of humanity's salvation lies a battlefield for the final conflict between good and evil.